2002
DOI: 10.1088/0953-2048/15/4/317
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting miniaturized antennas based on dual-mode cross-slotted patches

Abstract: The use of high-temperature superconducting films for the fabrication of antennas allows us to realize radiating structures that are small in size and have a very high efficiency. In this paper, we investigate the properties of a novel compact antenna obtained by crossing a square patch with diagonal and transverse slots. Single patch antennas, with both linear and circular polarization operating in the X-band, with a size reduction of about 40% as compared to conventional square patches, have been designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Similar to what was found for the dual-mode dual-stage filter, we have realized a quasi-elliptical response without using another external cross-coupling structure but simply by inverting the position of the diagonal slots [7]. Moreover, for this configuration, we have found that it is also possible to change, in the range of 1% of the central frequency, the position of the attenuation zeros by combining different positions of the two 50 feed line connections with respect to the centre of the stepped resonator.…”
Section: (B)) As a Function Of Thementioning
confidence: 59%
See 1 more Smart Citation
“…Similar to what was found for the dual-mode dual-stage filter, we have realized a quasi-elliptical response without using another external cross-coupling structure but simply by inverting the position of the diagonal slots [7]. Moreover, for this configuration, we have found that it is also possible to change, in the range of 1% of the central frequency, the position of the attenuation zeros by combining different positions of the two 50 feed line connections with respect to the centre of the stepped resonator.…”
Section: (B)) As a Function Of Thementioning
confidence: 59%
“…The layout of a designed four-pole filter is shown in figure 1(a). Briefly, the first and the last resonators are traditional stepped impedance resonators, while the second and third resonators are the orthogonal modes of the crossslotted square patch recently used in the design of filters and antennas [6,7].…”
Section: Filter Designmentioning
confidence: 99%
“…As compared with common superconducting materials such as YBa 2 Cu 3 O Y , La-based hightemperature superconducting (HTSC) possess some attracting features, such as high superconducting critical temperature (T C ), high critical current density (J C ), very low microwave surface resistance (R s ) and a good stability in moisture [16][17][18][19][20]. All of these properties merit potential superiority of La-based thin-film devices for electronic applications, ranging from superconducting quantum interference devices (SQUIDs) to superconducting microwave resonators and also other passive devices [21][22][23][24][25][26]. The effects of partial substitution of Y by La -atom on the growth mechanism and superconducting properties will be studied for the component La x Y 1-x Ba 2 Cu 3 O 7-δ at x=0, 0.20, 0.40, 0.50, 0.60 and 0.80 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the high temperature superconductors (HTSs) were discovered in 1986 [1], many studies have been made on the preparation of epitaxial HTS films because of their increasing application in many areas. One of the major applications of HTS thin films is in microwave devices [2][3][4][5][6] due to their much lower microwave surface resistance (R s ) than that of normal material and their high microwave power handling capability [7,8].…”
Section: Introductionmentioning
confidence: 99%